The Assessment of Peak Discharge Increment Due to Land Use Change in the Serang Welahan Drainage 1 (SWD 1) River, Central Java Province, Semarang : English - Elisabeth Sitorus, Jessica; Wisanggeni, Dimas Harya; Salsabila, Aulia Aisyah; Nugroho, Eka Oktariyanto; Badri Kusuma, Muhammad Syahril (Departemen Teknik Sipil dan Lingkungan IPB, 2024)
SWD1 River is located in one of those flood-prone areas in Central Java that generates flood hazards causing high risk to the surrounding rice fields and communities. However, a comprehensive study of flood hazards in SWD1 River has never been conducted. Nowadays, previous comprehensive flood studies in Indonesia only available for several very developed areas, such as the Jakarta Flood [1] – [5], Bandung Flood and Solo Flood , or new iconic area for mangrove conservation such as Langsa City . Most previous studies conclude that flood hazards in Indonesia are commonly generated by rain runoff, tides, and dam break flows, or a combination of these generators . Existing conditions show that SWD 1 is unable to accommodate runoff from the Wulan River, causing flooding. Based on rainfall data from BMKG, the maximum rainfall per month for a year reaches 323 mm. This study is an effort to analyze the impact of land use change.The research method used analysis of the influence of changes in CN (Curve Number) due to changes in land use on flood discharge as shown through changes in the Soil Conservation Service (SCS-CN) hydrograph on discharge and runoff volume. The selection of the SCS-CN method is due to its widespread adoption in various regions, its extensive use in numerous analytical studies, and its suitability for the characteristics of the watershed under review.The analysis results show that there has been a change in flood discharge from 2019 and 2022 with values of 366.920 and 371.154 m3/second. The discharge values did not change significantly because the CN values were as follows, 83.25 and 83.36. Through analysis, it can be seen that an increase in discharge of 1.14% from 2011 to 2022.The several alternatives are needed to reduce flooding, such as watershed conservation upstream, minimizing land use changes and building flood mitigation infrastructure downstream.